"Kick‐Starting" oxetane photopolymerizations. Issue 20 (8th August 2014) - Crivello, James V.
ABSTRACT In the presence of small amounts of 2, 2‐dialkyl‐, 2, 2, 3‐trialkyl‐, or 2, 2, 3, 3‐tetraalkyl substituted epoxides such as isobutylene oxide, 1, 2‐limonene oxide, and 2, 2, 3, 3, ‐tetramethyl oxirane, the photoinitiated cationic ring‐opening polymerizations of 3, 3‐disubstituted oxetanes are dramatically accelerated. The acceleration affect was attributed to an increase in the rate of the initiation step of these latter monomers. Both mono‐ and disubstituted oxetane monomers are similarly accelerated by the above‐mentioned epoxides to give crosslinked network polymers. The potential for the use of such "kick‐started" systems in applications such as coatings, adhesives, printing inks, dental composites and in three‐dimensional imaging is discussed. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2934–2946